The fusiform skin paddle in fibula free flap: a fusiform-designed skin paddle for maxillofacial soft defect reconstruction and reducing leg wound tension - Li, Shuai; Zheng, Xin; Cheng, Guo-Sheng; Mai, Hua-Ming; He, Qian-Ting; Wang, An-Xun (Frontiers in Oncology, 2024)
Object: To investigate the feasibility of leg wound closure and reconstruction of maxillofacial soft defect by a fusiform-designed skin paddle in fibula free flap (FFF).Method: Fifty patients who underwent FFF for reconstruction of maxillofacial soft defect were divided into two groups. The fusiform group (20 patients) was treated using a fusiformdesigned skin paddle in FFF (skin paddle width less than 2 cm), and leg wound was closed using primary suturing. Reconstruction of the maxillofacial soft defect or filling of dead space was achieved by folding the fusiform skin paddle. The conventional group (30 patients) was treated using the conventional-designed skin paddle (skin paddle width no less than 2.5 cm).The leg wound was closed using mattress suturing or skin graft, while reconstruction of the maxillofacial soft defect or filling of dead space by conventional way. The average postoperative length of hospital stay, healing time of leg wound, and post-surgical complications were recorded at least 6 months after the surgery.Result: Compared with traditional method, the fusiform-designed skin paddle reduced the average healing time of the leg wound (fusiform group: 11.05 days, conventional group: 14.77 days, P < 0.05). The average length-to-width ratio in fusiform group was significantly greater than that of in conventional group (fusiform group: 5.85, conventional group: 2.93, P < 0.05), and no difference was observed on the graft size of skin paddle between two groups (fusiform group: 23.13, conventional group: 27.13, P > 0.05). The post-surgical early complications of the leg wound in the conventional group were higher than that of in the fusiform group (fusiform group: 0%, conventional group: 6.67%), while the post-surgical late complication of the donor site between the two groups showed no case. Healing disorders of maxillofacial 3 / 19 soft reconstruction in the conventional group were higher than that of in the fusiform group (fusiform group: 5.26%, conventional group: 20.69%).Fusiform-designed skin paddle for closure of the leg wound and maxillofacial soft defect is a feasible alternative to the conventional-designed skin paddle. The fusiformdesigned skin paddle resulted in the less postoperative length of hospital stay, shorter healing time of leg wound and less complication.